Archaeobotanical analyses at Oldenburg 108, Burgstrasse, Lower Saxony, Germany - counts - Bittmann, Felix (Niedersächsisches Institut für historische Küstenforschung, Wilhelmshaven, 2021)
From two profiles of an archaeological trench in the centre of the city Oldenburg 108, Burgstr. , Lower Saxony, two largely overlapping cores, 50 (length) x 10 (width) x 5 (thickness) cm, of highly organic sediments were taken and one sample of about 2 l in a plastic bag from the northern profile 44 in 2005 (June 2nd). Subsamples were taken following the layers in the metal boxes, sieved in the laboratory using stacked sieves of mesh-sizes 1, 0.71 and 0.3 mm and botanical macroremains were picked out using a microscope (magnification 10x-50x), identified and counted in the course of 2006. The identified remains (seeds, fruits, vegetative remains, zoological remains) dating to the Late Medieval were assigned to ecological groups allowing the reconstruction of the environmental conditions at the time of deposition. The aims of the analyses were to reveal which human activities took place at the place, which cultural plants can be traced, which structures were present, what kind of sediment has been investigated (the preliminary assumption by the archaeologists has been peat) and how old are the remains/features.